PENGGUNAAN WINDOW WIDTH DAN WINDOW LEVEL PADA PEMERIKSAAN COMPUTED TOMOGRAFY SCANNER THORAX DENGAN KLINIS ANEURISMA AORTA DI RUMAH SAKIT AL ISLAM BANDUNG: THE ROLE OF WINDOW WIDTH and WINDOW LEVEL ON THE MANAGEMENT OF THORAX COMPUTED TOMOGRAFY SCANNER WITH THE CLINICAL OF AORTA ANEURISMA at BANDUNG AL ISLAM HOSPITAL - ningrum, Surdiyah Asri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2024)
Setting the parameters of Window Width and Window Level on CT Scan Thorax examination using contrast media can produce a good image of the lungs and aorta. The purpose of this study is to find out the right window setting so as to produce a good image in the case of Aortic Aneurysm. This type of research is descriptive qualitative with a case study approach. The results showed that the effect of window width and Window Level parameter settings on the lung window and mediastinum window provided optimal image quality results of abnormalities in the lungs and surrounding anatomical structures.